De l'usage du référentiel d'activités pour s'autoriser à devenir formateur donc guide et accompagnateur - Valérie Guillemot; Michel Vial (Université de Provence, 2009)
In this article we present the results of a series of six interviews carried out with professional trainers and accompanists (coaches) from the field of adult education. Individual methods and practices are explored.  With the study arise various questions of identity and ethical challenges facing these professionals.  Our results suggest the possible interest of applying a grid of professional skills in the process of self-assessment especially with regards to the aspect of accompaniment (coaching) in their professional activity.